Policy analytical capacity: The supply and demand for policy analysis in government. Issue 3 (1st September 2015) - Howlett, M
Abstract: ''Policy analytical capacity'' is an important component of overall policy capacity, bringing together individual level analytical skills (competencies) and resources (capabilities) needed for the systematic evaluation of policy alternatives and practices. Despite the existence of a large body of literature on policy analysis, a more complete picture of the roles played by policy analysts in policy appraisal is needed if the nature of contemporary policy work and formulation activities and the impact and influence of higher and lower levels of capacity of governments in this area are to be better understood.